2014
DOI: 10.1186/1471-2458-14-198
|View full text |Cite
|
Sign up to set email alerts
|

Social and health policies or interventions to tackle health inequalities in European cities: a scoping review

Abstract: BackgroundHealth inequalities can be tackled with appropriate health and social policies, involving all community groups and governments, from local to global. The objective of this study was to carry out a scoping review on social and health policies or interventions to tackle health inequalities in European cities published in scientific journals.MethodsScoping review. The search was done in “PubMed” and the “Sociological Abstracts” database and was limited to articles published between 1995 and 2011. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 36 publications
4
48
0
2
Order By: Relevance
“…Therefore, it is important to design policies that act across the whole gradient and to address the people at the bottom of the social gradient and the people who are most at risk as described in the Review of social determinants and the health divide in the WHO European Region [ 29 ]. In similar reviews the authors found that most of the parent/infant stimulation programs dealt with “high-risk” children or interventions which focused almost exclusively on downstream initiatives in deprived areas [ 57 ]. Furthermore, the studies which were not targeted did not describe in their findings whether they had a differential impact for disadvantaged groups.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to design policies that act across the whole gradient and to address the people at the bottom of the social gradient and the people who are most at risk as described in the Review of social determinants and the health divide in the WHO European Region [ 29 ]. In similar reviews the authors found that most of the parent/infant stimulation programs dealt with “high-risk” children or interventions which focused almost exclusively on downstream initiatives in deprived areas [ 57 ]. Furthermore, the studies which were not targeted did not describe in their findings whether they had a differential impact for disadvantaged groups.…”
Section: Discussionmentioning
confidence: 99%
“…Disadvantaged populations tend to have worse health and higher morbidity and mortality (11,12). In agreement with this statement, the final report of the World Health Organization Commission on the Social Determinants of Health (CSDH), published in 2008, affirmed that social injustice was killing on a grand scale, with a toxic combination of 'poor social policies and programmes, unfair economic arrangements, and bad politics' being responsible for producing and reinforcing health inequalities (13).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, social capital interventions might contribute to reduce health inequalities by addressing social determinants of health 70. Accordingly, we encourage an inclusive approach when improving social capital by considering the disadvantage categories of the PROGRESS Plus framework in the design, evaluation and reporting.…”
Section: Discussionmentioning
confidence: 99%